Analisis Faktor-Faktor Yang Mempengaruhi Produktivitas Kopi Robusta Terhadap Peningkatan Pendapatan Ekonomi Petani - Parinton Banjarnahor; Esra Tarigan (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2022)
The research aims to analyze productivity, influential factors and the factors that most affect the economic income of robusta coffee farmers farmers in Sempung Polling Village Laeparira District Dairi Provinsi North Sumatra. The location of the study is determined purposively. The method used is the survey method and sample selection is determined by choosing 52 respondents robusta coffee farmers in Sempung Polling Village Laeparira Subdistrict. The results showed that the average production of robusta coffee farmers in Sempung Polling Village of Laeparira District of Dairi Regency amounted to 919.30kg / ha. Simultaneously production, land area, and labor have a real effect simultaneously on the economic income of Robusta coffee farmers. Production, from regression results obtained a calculated value of (-0.597 and Sig. of 0.153. The value t calculates (-0.597) ≤ t table (1.995) then H0 is accepted. This means that production has an unreal effect on farmers' economic income, land area, from regression results obtained by the value of 1,098 and Sig. 0.278 t-count value 1,098 ≤ 1,995 then Ho accepted means the area of robusta coffee plant land has a real effect on farmers' economic income. Labor from regression results obtained a calculated value of -1,230 and Sig. 0.030. The value t calculated (-2,237) < t Table (1,995) then Ho accepted. This means that the amount of labor has no real effect on the economic income of Robusta coffee farmers. Based on the partial survey of labor is the most influential factor on robusta coffee production factor in Sempung Polling Village Laeparira District Dairi District of North Sumatra Province.